2019
DOI: 10.1130/g45725.1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for molecular structural variations in the cytoarchitectures of a Jurassic plant

Abstract: In this study, we investigate the molecular structural characteristics of organic remains in various cellular organelles from a 180 Ma Jurassic royal fern belonging to the Osmundaceae family of ferns, and compare their carbon isotopic compositions to a now-living species of royal fern (Osmunda regalis). We discovered molecular structural variations indicated by Raman and infrared spectral parameters obtained from various fossilized cellular organelles. The organic remains preserved in the chromosomes and cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This may be complicated royalsocietypublishing.org/journal/rsfs Interface Focus 10: 20200015 by the nucleus-like decay artefacts in bacterial-grade microbes [2][3][4], but the history of debate over the identification of nuclei in the Weng'an fossils demonstrates that eukaryote organelles can be discriminated based on consistency of shape, size and, for instance, how these change through cell division [19,20]. There are a number of credible examples of nuclei preserved in Phanerozoic fossil eukaryotes [5][6][7][8][9][10][11][12][13][14]. Our taphonomy experiments demonstrate the decay resistance of nuclei and the feasibility of their fossilization, both of which are corroborated by our characterization of nuclei in the Proterozoic Weng'an embryo-like fossils.…”
Section: Implications For Elucidating the Fossil Record Of Eukaryotesmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be complicated royalsocietypublishing.org/journal/rsfs Interface Focus 10: 20200015 by the nucleus-like decay artefacts in bacterial-grade microbes [2][3][4], but the history of debate over the identification of nuclei in the Weng'an fossils demonstrates that eukaryote organelles can be discriminated based on consistency of shape, size and, for instance, how these change through cell division [19,20]. There are a number of credible examples of nuclei preserved in Phanerozoic fossil eukaryotes [5][6][7][8][9][10][11][12][13][14]. Our taphonomy experiments demonstrate the decay resistance of nuclei and the feasibility of their fossilization, both of which are corroborated by our characterization of nuclei in the Proterozoic Weng'an embryo-like fossils.…”
Section: Implications For Elucidating the Fossil Record Of Eukaryotesmentioning
confidence: 99%
“…In large part, this stems from experiments which show that cytoplasmic shrinkage in decaying bacteria can produce nucleus-like remains [2][3][4]. However, it does not follow from these experiments that nuclei cannot be preserved and, indeed, there are a number of credible claims of fossilized nuclei [5][6][7][8][9][10][11][12][13][14]. Claims of nuclei and even nucleoli preserved in association with embryo-like fossils from the approximately 609 Mya Ediacaran Weng'an Biota [15][16][17][18][19][20] have proven especially contentious [1,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to morphological characters, studies of remnant organic constituents within fossils have shown to be important for supporting taxonomic and phylogenetic assignations (D'Angelo 2010(D'Angelo , 2015Vajda et al 2017) and even reconstructing overall architecture of fragmented fronds (D'Angelo et al 2018;Zodrow et al 2019). Infrared (IR) microspectroscopy has proven to be a particularly useful technique for this purpose because of its nondestructive nature, chemical specificity, and ability to analyze minute sam-ple areas, which enables analysis of, for instance, fossil pollen and spores (e.g., Steemans et al 2010;Fraser et al 2012;Jardine et al 2016Jardine et al , 2019Dupont-Nivet 2021), minute leaf fragments (Vajda et al 2017), fossil resin (Seyfullah et al 2015), and even fossilized cellular organelles (Qu et al 2019). IR microspectroscopy has been employed for the identification of organic compounds in various fossils, such as pre-Cambrian stromatolites and fungi (Qu et al 2015), but also for advanced multicellular organisms.…”
Section: Introductionmentioning
confidence: 99%
“…61 It does not require thin sections and can be used non-destructively on, e.g., fossils. 62 The downside of Raman microspectroscopy is the enormous amount of spectral information contained in each cell wall spectrum. Even more so than in FTIR, the numerous bonds in the sample result in a highly convoluted spectrum, making the quantification of isolated bands difficult.…”
Section: ■ Methods For Lignin In Situ Analysismentioning
confidence: 99%